Assessing the relative influence of hospital and surgeon volume on short‐term mortality after radical cystectomy. (10th March 2017) - Waingankar, Nikhil; Mallin, Katherine; Smaldone, Marc; Egleston, Brian L.; Higgins, Andrew; Winchester, David P.; Uzzo, Robert G.; Kutikov, Alexander
Abstract : Objectives: To assess the relationship between surgeon (SV) and hospital volume (HV) on mortality after radical cystectomy (RC). Patients and Methods: We queried the National Cancer Database (NCDB) for adult patients undergoing RC between 2010 and 2013. We calculated average volume for each surgeon and hospital. Using propensity‐scored weights for combined volume groups with a proportional hazards regression model, we compared the associations between HV and SV with 90‐day survival after RC. Results: A total of 19 346 RCs were performed at 927 hospitals by 2 927 surgeons in the period 2010–2013. The median (interquartile range) HV and SV were 12.3 (5.0–35.5) and 4.3 (1.3–12.3) cases, respectively. For HV, 90‐day unadjusted mortality was 8.5% in centres with <5 cases/year (95% confidence interval [CI] 7.7–9.3) and 5.6% in those with >30 cases/year (95% CI 5.0–6.2). For SV, 90‐day mortality was 8.1% for surgeons with <5 cases/year (95% CI 7.6–8.6) and 4.0% for those with >30 cases/year (95% CI 2.8–5.2; all P < 0.05). The 30‐day mortality rate was lowest for the combined HV–SV groups with HV >30, ranging from 1.6% to 2.1%. Conclusions: In hospitals reporting to the NCDB, volume was associated with improved mortality after RC. These associations appear to be driven by hospital‐ rather than surgeon‐level effects. An elevated SV had a beneficial effect on mortality at the highest‐volume hospitals. These findings inform efforts to regionalize complex surgical care and improve quality at community and safety net hospitals.